Implementation of Geogebra in Improving Understanding of Geometry Concepts in Junior High School Students - Nur Aisyah; Nirfayanti Nirfayanti; Dedy Setyawan (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2025)
In the digital era, the integration of information and communication technology in education is essential for enhancing students' learning experiences. This study investigates the effectiveness of GeoGebra, a dynamic mathematics software, in improving eighth-grade students' understanding of geometric concepts at MTS Negeri 1 Maros. Employing a quasi-experimental design, the research involved two groups: an experimental class using GeoGebra and a control class utilizing conventional teaching methods. Data were collected through pre-tests, post-tests, and student questionnaires. Results indicated a significant improvement in the experimental class, with an average post-test score of 84.82 compared to 71.25 in the control class, and an N-Gain of 0.804 versus 0.636, respectively. Statistical analysis confirmed a significant difference between the two groups (p < 0.001), indicating that GeoGebra effectively enhances students' understanding of geometry. Additionally, student responses were overwhelmingly positive, with 82% expressing enjoyment in learning with GeoGebra. This study concludes that GeoGebra not only improves academic performance but also fosters a more engaging and interactive learning environment, making mathematics more accessible and enjoyable for students.